PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH BERBANTUAN FLASHCARD TERHADAP HASIL BELAJAR PPKN KELAS II SD - Andreas Sihombing; Juliana; Patri Janson Silaban; Irmina Pinem; Heka Maya Sari Sembiring (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to determine (1) To determine the process of implementing the make a match learning model in class II of SD Yayasan Tunas Harapan in the 2024/2025 academic year in learning activity 1 five symbols of Pancasila unit 1 Pancasila Dasar Negaraku (2) To determine student learning outcomes in learning activity 1 five symbols of Pancasila unit 1 Pancasila Dasar Negaraku before using the make a match model in class II of SD in learning activity 1 Pancasila Dasar Negaraku and elements of the five symbols of Pancasila (3) To determine the effect of the make a match model on student learning outcomes in learning activity 1 five symbols of Pancasila unit 1 Pancasila Dasar Negaraku class II SD Yayasan Tunas Harapan in the 2024/2025 academic year. The instruments used in this study consisted of questionnaires and test instruments. The population of this study was all class II of SD Yayasan Tunas Harapan totaling 32 students. The results of this study showed that student learning outcomes were classified as good with an average of 79.09 with a correlation result of 0.796 which means r count (0.796) ≥ r table (0.349) then Ha is accepted, so there is an influence between the Make A Match Type Cooperative Learning Model Assisted by Flashcards on Student Results of Class II SD Yayasan Tunas Harapan. The results of the T-test study where t count ≥ t table are 7.324. If t count ≥ t table or 7.324 ≥ 2.048 then it can be said that there is an influence of the Make A Match Type Cooperative Learning Model Assisted by Flashcards on Student Learning Outcomes and shows a significant positive influence, thus Ha is accepted, namely there is an influence between the Make A Match Type Cooperative Learning Model Assisted by Flashcards on Student Learning Outcomes.